Вольтер и Россия - Михайлов Андрей Дмитриевич (Сравнительное литературоведение, 1999)
Экземпляры: КХ (20000111) / Инвентарный номер: 1033927 / Цена: 20.00 / Сис.шифр: 87.3(3/8) / Авт.знак: В 71 / ГРНТИ: 03 / ББК: 87.3(4Фра)5